A SMARTPHONE-BASED ADAPTIVE LEARNING APPROACH TO ENHANCE STUDENTS’ LEARNING OUTCOMES IN ENGLISH SUBJECT - Farhanirahma; Lidiyatul Izzah; Muhamad Sofian Hadi (Getsempena English Education Journal, 2021)
The purpose of this study is to improve student learning outcomes through a smartphone-based adaptive learning approach to 28 students from the 11th grade students in the 2020/2021 academic year. It is important to consider the educational context when evaluating the barriers to adopting adaptive learning approaches on digital platforms. The method used in this study is a quantitative method, everything observed was measured and converted into numbers so that statistical analysis techniques were possible. The author chose a pre-experimental design with a pre-test post-test group design, in which a group of subjects is taken from a certain population and performed in a pre-test and then undergoes treatment one after another. After the treatment, the person received a posttest to measure the learning outcomes of the group. The grades given have the same weight. The difference between the results of the pretest and the post-test shows the results of the treatment performed. The results of this study were analyzed using the t-test by comparing the mean values of the pre-test and post-test. The results showed that the t-observation value (7.8) was higher than the t-table value (1.70562) at the 5% significance level. It can be concluded that the learning approach adaptive smartphone-based improves student learning outcomes in English subjects.